(3aJM GdhUjO HJGQjN YdeGA eQGZI GdUYjOs - (3eMeO Hf eMeO Hf MGeO Hf eMeO GdLQLGhj GdeQGZj,J (B1355 (3g` s
(3ChdgG (B:s
(3hHYO deG cGfJ GdHdOI GdeSeGI HGdeQGZI ef HdGO GdUYjO PGJ GdbOQ hGdTQa hGdWGdY GdSYjO HXghQ GdCaGVd ajgG bOjekG hMOjKkG s
(3BNQgG (B:s
(3hHPdc UGQ JGQjNkG NGUkG Hef fHY ef gPg GdHdOI eQGZI s
(3HBNQgG agQSJs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B81 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B204s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B307 s
Keywords: (3GdJGQjNs